Nonsense-mediated mRNA decay efficiency varies in choroideremia providing a target to boost small molecule therapeutics. (23rd January 2019) - Sarkar, Hajrah; Mitsios, Andreas; Smart, Matthew; Skinner, Jane; Welch, Ailsa A; Kalatzis, Vasiliki; Coffey, Peter J; Dubis, Adam M; Webster, Andrew R; Moosajee, Mariya
Abstract: Choroideremia (CHM) is an x-linked recessive chorioretinal dystrophy, with 30% caused by nonsense mutations in the CHM gene resulting in an in-frame premature termination codon (PTC). Nonsense-mediated mRNA decay (NMD) is the cell's natural surveillance mechanism that detects and destroys PTC-containing transcripts, with UPF1 being the central NMD modulator. NMD efficiency can be variable amongst individuals with some transcripts escaping destruction, leading to the production of a truncated non-functional or partially functional protein. Nonsense suppression drugs, such as ataluren, target these transcripts and read-through the PTC, leading to the production of a full length functional protein. Patients with higher transcript levels are considered to respond better to these drugs, as more substrate is available for read-through. Using Quantitative reverse transcription PCR (RT-qPCR), we show that CHM mRNA expression in blood from nonsense mutation CHM patients is 2.8-fold lower than controls, and varies widely amongst patients, with 40% variation between those carrying the same UGA mutation [c.715 C>T; p.(R239 * )]. These results indicate that although NMD machinery is at work, efficiency is highly variable and not wholly dependent on mutation position. No significant difference in CHM mRNA levels was seen between two patients' fibroblasts and their induced pluripotent stem cell-derived retinal pigment epithelium. There was no correlation between CHM mRNA expression and genotype, phenotype or UPF1 transcript levels. NMD inhibition with caffeine was shown to restore CHM mRNA transcripts to near wild-type levels. Baseline mRNA levels may provide a prognostic indicator for response to nonsense suppression therapy, and caffeine may be a useful adjunct to enhance treatment efficacy where indicated.